Poster on mobilizing agro-biodiversity and social networks to cope with adverse effects of climate and social changes: experiences from Kitui, Kenya. - Fujimura, R.; Morimoto, Y.; Maundu, P.; Inoue, M.; Eyzaguirre, Pablo B. (2012)
Farmers of Kitui District of Kenya mainly depend on subsistence farming and local resources from the immediate environment for their livelihood. Private self help groups serve as forums for operating a microcredit loan and providing labour during planting,weeding and harvesting. Such groups also assist members to exchange seeds and plants. Social ties are essential for community welfare as households facing food shortages turn to their relatives for money, seeds or food. This paper uses ethno-botanical approaches to assess farmers management practices of crop diversity and wild food plants in relation to their socio-economic conditions. Paticular focus has been put on farmers activities such as crop production, animal keeping, hunting, and off-farm employment as a response to climatic and social changes. Wealth ranking method was performed in a forcus group disscussion as a preliminary process of the survey which identifed 12 representative families from the target community. Farmers' activities were monitored for 2 months (during the rain season, Nov.-Dec.2011), through field visits and participant observations, interviews using open-ended questions. Results show that farmers in Kitui often maintain different farms located in ecological mosaics to minimize risks of total crop failure. Social networks are maintained and are more important among women who may belong to one or more social groups. Families maintain strong ties with relatives working in urban areas for remittances. On the farm, farmers tend to grow several varieties of the crop. Typically, they grow both quick-maturing and late-maturing crops in order to harvest averagely in every period. Crops are mixed to ensure high agrobiodiversity and hence chances of at least some crops succeeding under highly variable weather conditions. Deep rooted perennials and biennials are preferred when extreme drought is expected. These strategies are combined to ensure that food provisions are available to the household through bad seasons.